PENGARUH KARAKTERISTIK AUDITEE PADA PERGANTIAN AUDITOR - Sarasintya, Ida Ayu Agung; Lely Aryani M., Ni Kt (E-Jurnal Akuntansi, 2014)
When client change their auditor while there is no rule that requires changing, what happens is one of two things: the auditor resign or they got fired by the client. Whichever happened, the attention is the reason why it happened and where the client will move. The observation to determine the factors that affect the company did auditors switching, using five variables: the size of the client, management change, merger, expansion, and public ownership. The data being used is from financial statements of bank which is listed in the Indonesia Stock Exchange in 2008-2012 period. Analysis of the findings has shown that the independent variables (the size of the client, merger, expansion, and public ownership) had no effect on the change of auditors by bank listed on the Indonesia Stock Exchange from 2008 until 2012.
Keywords: auditor switching, auditing, auditee characteristic